Clinical Features and Genetic Analysis of Pediatric Patients with Alagille Syndrome Presenting Initially with Liver Function Abnormalities - Liu, Yan; Wang, Hong; Dong, Chen; Feng, Jie-xiong; Huang, Zhi-hua (Current medical science, 2018)
Summary Alagille syndrome (AGS) is a multisystem disorder and caused by mutations in JAG1 or NOTCH2 gene. The diagnosis of AGS is hampered by its highly variable clinical manifestations. We performed a retrospective analysis on 16 children diagnosed as having AGS in recent five years in our hospital. Cholestasis was seen in 15 patients (93.8%), heart disease in 12 (75%), characteristic facies in 7 (43.8%), and butterfly vertebrae in 7 (43.8%). Ophthalmology examination was not performed on all the patients. Further, serum biochemical parameters were compared between AGS and 16 biliary atresia (BA) patients who were confirmed by surgery. Elevated liver enzymes were seen in all the patients. Serum total cholesterol (TC) ( P =0.0007), alanine aminotransferase (ALT) ( P =0.0056), aspartate aminotransferase (AST) ( P =0.0114), gamma-glutamyl transferase (GGT) ( P =0.035) and total bile acid (TBA) levels ( P =0.042) were significantly elevated in AGS patients compared to those in BA cases. However, there were no significant differences in serum total bilirubin (TB), conjugated bilirubin (CB) and albumin (ALB) between the two groups. We identified 14 different JAG1 gene variations and 1 NOTCH2 gene mutation in 16 Chinese AGS patients. Our study suggested clinical features of AGS are highly variable and not all patients meet the classical diagnostic criteria. It was suggested that hypercholesterolaemia and significantly elevated GGT, TBA and ALT may be helpful to diagnose AGS. Genetic testing is integral in the diagnosis of AGS.